ECDI‐fixed donor splenocytes prolong skin allograft survival by promoting M2 macrophage polarization and inducing regulatory T cells. Issue 11 (17th October 2019) - Zhou, Bo; Zhang, Yuan; Zhang, Dongliang; Zhang, Yun; Xie, Jiangang; Zhang, Xuexin; Ding, Jianke; Su, Yingjun; Guo, Shuzhong; Zhuang, Ran
Abstract: Rejection is a common complication of allogeneic tissue transplantation. Fixation of splenocytes (SP) with 1‐ethyl‐3‐(3'‐dimethylaminopropyl)‐carbodiimide (ECDI) induces immune tolerance in recipients post‐transplantation; however, the mechanism underlying this effect remains unclear. Here, we determined the mechanisms of ECDI‐fixed donor SP (ECDI‐SP) in inducing tolerance in skin allograft transplantation. C57BL/6‐recipient mice that received Balb/c full‐thickness skin transplants with two infusions of donor‐derived ECDI‐SP, along with rapamycin showed superior skin allograft survival and lower inflammatory cell infiltration than mice that received rapamycin‐only treatment. In ECDI‐SP‐treated mice, the levels of anti‐inflammatory cytokines such as interleukin (IL)‐10 in sera were markedly increased, whereas the expression of inflammatory cytokines was significantly suppressed. Splenic macrophages were significantly polarized to the alternative activated macrophage (M2) phenotype, with expansion of CD4 + Foxp3 + regulatory T cells (Tregs) in the spleen and draining lymph nodes. Allostimulatory activity of ECDI‐SP in vitro and donor‐specific ex vivo hyporesponsiveness were observed. C57BL/6 macrophages engulfed allogeneic Balb/c‐derived ECDI‐SP, polarized to the M2 phenotype, with pronounced cAMP response element‐binding (CREB) protein phosphorylation. By facilitating increased IL‐10 expression, ECDI‐SP induced M2 polarization and Treg production, inhibiting effector T‐cell proliferation. Thus, ECDI‐SP modulates macrophage M2 polarization by increasing CREB phosphorylation and promoting Treg production to suppress allogeneic skin graft rejection.